Grottesangen i Johannes V. Jensens og Viktor Rydbergs regi - Svendsen, Erik (Danske Studier, 2024)
The authors Viktor Rydberg from Sweden and Johannes V. Jensen from Denmark both recreated Grottasǫngr from Snorri’s Edda, Rydberg in 1891 and Jensen both in Kongens Fald (1900-01) and Digte 1906. Remarkably, it is the proclaimed idealist Rydberg who uses the original as a means to social criticism, whereas Jensen, the materialist, in a much more abstract manner points out how the work of the singing maidens Fenja and Menja ends up as a hymn to decline and fall. The article argues that whereas Rydberg calls for compassion and love among people, Jensen pays tribute to a mythical order.